A case of myocardial metastasis of bladder cancer - D. V. Shatov; P. E. Grigoriev; V. V. Shalanin (Бюллетень сибирской медицины)
The case of metastatic heart damage manifesting by a clinical picture of acute myocardial infarction in a patient with urothelial carcinoma of the urinary bladder is described. A 69-year old patient was admitted with the symptoms of acute myocardial infarction from the neurological department, where he was hospitalized due to a space-occupying lesion of the right hemisphere of the brain, which manifested in a convulsive episode with the development of leftsided spastic hemiparesis. After coronary angiography, percutaneous coronary intervention was performed for the lesions of the anterior interventricular branch of the left coronary artery. Despite the complex of the therapeutic  measures, the patient died. A pathological study revealed urothelial carcinoma of the bladder with distant metastases to the brain and myocardium. This clinical case demonstrates the situation of intravital diagnosis of metastatic myocardial lesions, which requires a determination of the treatment approach in the described category of patients.